The innovator's dilemma : when new technologies cause great firms to fail - Christensen, Clayton M. (Management of innovation and change series., 1997)
This book takes the radical position that great companies can fail precisely because they do everything right. It demonstrates why outstanding companies that had their competitive antennae up, listened astutely to customers, and invested aggressively in new technologies still lost their market leadership when confronted with disruptive changes in technology and market structure. And it tells how to avoid a similar fate. Using the lessons of successes and failures of leading companies, The Innovator's Dilemma presents a set of rules for capitalizing on the phenomenon of disruptive innovation. These principles will help managers determine when it is right not to listen to customers, when to invest in developing lower-performance products that promise lower margins, and when to pursue small markets at the expense of seemingly larger and more lucrative ones.